2021
DOI: 10.1126/sciadv.abh1097
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the Pr-Pfr long-range signaling mechanism of a full-length bacterial phytochrome at the atomic level

Abstract: A bacterial phytochrome reversibly interconverts between a parallel and antiparallel dimeric arrangement during photoconversion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…The sequence of events that leads to such structural changes however is still not understood, due to the multiple time and space scales involved in the process. 16,20,21,28,29,[32][33][34][35][36][37][38][39][40] Thanks to spectroscopic investigations, we know that the photocycle of bacteriophytochromes involves at least two intermediate states, namely Lumi-R and Meta-R 36,[41][42][43] . The former arises from the photoisomerization; then, on the microsecond time scale, thermal relaxation processes lead to the formation of the Meta-R intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of events that leads to such structural changes however is still not understood, due to the multiple time and space scales involved in the process. 16,20,21,28,29,[32][33][34][35][36][37][38][39][40] Thanks to spectroscopic investigations, we know that the photocycle of bacteriophytochromes involves at least two intermediate states, namely Lumi-R and Meta-R 36,[41][42][43] . The former arises from the photoisomerization; then, on the microsecond time scale, thermal relaxation processes lead to the formation of the Meta-R intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…This dark reversion can be considered a rare event with a specific time scale depending on the type of phytochrome ranging from minutes to hours. 33 , 59 Below, we explain how the dark reversion can be rationalized from a thermodynamical point of view.…”
Section: Resultsmentioning
confidence: 99%
“… 30 However, it has been suggested that the chromophore fluctuations are more complex when a molecular switch is embedded in the protein environment. 5 , 31 33 What is arguably more important, experimental results have shown a possible existence of thermally dependent states of various phytochromes, 34 likely connected to the concept of weakly coupled equilibria. 35 , 36 It is unknown how such states relate to the thermal dark reversion of Pfr to Pr at the atomistic level.…”
Section: Introductionmentioning
confidence: 99%
“…1). Despite the numerous studies appeared so far, 13,17,18,27,28,34,[37][38][39][40][41][42][43][44] there is no consensus on the exact mechanism and the timing of the photoisomerization, neither we know the structures of the suggested intermediates and the molecular interactions that allow the propagation of the chromophore structural changes first to the binding pocket, and then to the entire protein.…”
Section: Introductionmentioning
confidence: 99%